2014
DOI: 10.5694/mja12.11175
|View full text |Cite
|
Sign up to set email alerts
|

A framework for overcoming disparities in management of acute coronary syndromes in the Australian Aboriginal and Torres Strait Islander population. A consensus statement from the National Heart Foundation of Australia

Abstract: Aboriginal and Torres Strait Islander patients with acute coronary syndromes (ACS) experience lower intervention rates and poorer outcomes compared with non-Indigenous patients. A broad range of geographical, cultural and systemic factors contribute to delays and suboptimal treatment for ACS. Every Indigenous ACS patient, regardless of where they live, should be able to expect a coordinated, patient-centred pathway of care provided by designated provider clinical networks and supported by Indigenous cardiac co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 10 publications
2
31
0
Order By: Relevance
“…To further examine the causes of the disparity in angiography rates, we undertook a medical record review of all Aboriginal ACS admissions in the hospital data, matched with data for a non‐Aboriginal cohort. This information provided insight into the medical decision‐making processes for Aboriginal ACS patients and confirmed that a negative hospital experience, bias based on complex comorbidities or presumed adherence to medications that favoured conservative management, and patient choice were implicated in the difference in angiography rates 6 , 14 , 15 …”
Section: Discussionmentioning
confidence: 64%
“…To further examine the causes of the disparity in angiography rates, we undertook a medical record review of all Aboriginal ACS admissions in the hospital data, matched with data for a non‐Aboriginal cohort. This information provided insight into the medical decision‐making processes for Aboriginal ACS patients and confirmed that a negative hospital experience, bias based on complex comorbidities or presumed adherence to medications that favoured conservative management, and patient choice were implicated in the difference in angiography rates 6 , 14 , 15 …”
Section: Discussionmentioning
confidence: 64%
“…However, disparities in ACS care for Indigenous people are well documented 12 . Here, we present a practical application of the guidelines for use in the Indigenous setting 13 …”
Section: Ischaemic Heart Diseasementioning
confidence: 99%
“…Enrolment in cardiac rehabilitation programs is beneficial after ACS, 13 but participation rates of Indigenous people are low. Reasons for this include distance, extended family responsibilities, socio‐cultural inappropriateness of programs, poor understanding of cardiac rehabilitation and the younger age of the Indigenous population with ACS (as patients in their 20s or 30s are less compliant and less likely to accept clinical recommendations).…”
Section: Ischaemic Heart Diseasementioning
confidence: 99%
“…There is a lack of sustained lockstep measures addressing one issue from multiple angles (Box 4 ). Exceptions include work from Brown et al , which provide strong foundations, with elements that are implementable [47], to continue a program of work [50-54]. …”
Section: Does Traditional Indigenous Life-styles Represent An Impedimmentioning
confidence: 99%